Agrarian Reform in Conflict Areas: The Bondoc Peninsula Experience - Carranza, Danilo (Kasarinlan: Philippine Journal of Third World Studies; Vol 26 No 1-2 (2011): Food Sovereignty in Southeast Asia, 2012)
This paper explains the historical evolution of the reform-oriented peasant movement in Bondoc Peninsula, and the causes and consequences of the violent opposition to its initiatives by landlords and the armed movement in the area.
Keywords: agrarian reform; peasant movements; Bondoc Peninsula; rural violence